School Administrative Factors Affecting Academic Administration Excellence of Schools Under Khon Kaen Primary Educational Service Area Office 1 - Sanan, Ancharee; Eungpuang, Arkom (Journal of Graduate MCU KhonKaen Campus, 2025)
The objectives of this research were to: (1) examine the factors of school administration under the Office of Khon Kaen Primary Educational Service Area 1; (2) investigate the level of academic administration excellence of schools in the area; and (3) analyze the administrative factors affecting academic administration excellence. The sample consisted of 317 participants, including 35 school administrators and 282 teachers, selected through stratified random sampling based on job positions. The research instrument was a five-point rating scale questionnaire comprising three sections, with reliability coefficients of .752 and .790. Data were analyzed using frequency, percentage, mean, standard deviation, and Stepwise Multiple Regression Analysis. The findings revealed that: 1) the overall level of school administration factors was at a high level, with personnel development being the highest-rated factor, while administrative leadership was the lowest 2) the overall excellence of academic administration was also rated at a high level, with teacher quality receiving the highest mean score and administrator quality the lowest 3) three administrative factors significantly affected academic administration excellence at the .05 level: teacher work motivation (β = .527), personnel development (β = .384), and organizational structure (β = –.228). These variables collectively explained 82.70% of the variance in academic administration excellence (R²=.827)